PUBLIC VALUE PENGGUNAAN TRANSPORTASI UMUM KERETA CEPAT JAKARTA-BANDUNG DI STASIUN TEGALLUAR SUMMARECON - Nurina Afifah Khansa; Nina Widowati (Journal of Management and Public Policy, 2026)
The high growth of community mobility in the Bandung and Jakarta areas has caused various transportation problems, especially traffic congestion and dependence on private vehicles. The presence of the Jakarta-Bandung Fast Train (Whoosh) is expected to be a transportation solution that can improve travel efficiency and provide public value to the community. However, in its implementation, there are still various obstacles that affect the optimization of the use of this service, especially at the Summarecon Tegalluar Station. This study aims to analyze the public value in the use of the Jakarta-Bandung Fast Train public transportation at Tegalluar Summarecon Station. The study uses a qualitative descriptive method with data collection techniques through interviews, observation, and documentation. The research informants consisted of high-speed train service users and parties related to service operations. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the creation of public value in the Whoosh High-Speed Train service at Tegalluar Station has not been fully optimized. Several aspects, such as user satisfaction and service comfort, have been fulfilled through adequate facilities and a fast travel experience. However, there are still obstacles in terms of accessibility, integrated transportation, and ease of access to the station, which affect the effectiveness of service use by the community. In conclusion, high-speed rail services have great potential in creating public value, but require improved intermodal integration, improved accessibility, and strengthened coordination between stakeholders. Therefore, it is recommended that a more integrated connecting transportation system be developed and the quality of access infrastructure to the Summarecon Tegalluar Station be improved.